PENGARUH PRODUK , HARGA DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PELANGGAN PENGGUNA JASA DI JNE MOJOKERTO - hartono hartono (PROFIT, 2018)
Marketing services is very important for a service company in order to market a product company into the market in accordance with the target so that the product is known in the community and consumed by the community. Therefore, this study aims to examine various factors that can influence the decisions of customer service users of PT JNE Mojokerto City. Object in this research is 100 customer, using multiple linear regression technique proved that hypothesis which sounded suspected product, price and service quality influence on customer service user decision acceptable by using F count equal to 3,213. From the calculation of the above three variables turns out that product variables have the strongest influence (dominant) supported with the result r = 0.224 then the service quality variable r = 0.199 and then the variable Price r = -0,033. Through this research, the suggestion that can be submitted is PT JNE Kota Mojokerto need to give big portion of attention related to imaging product image and no less important for price sector and service quality need to be considered.